Two new species of Asphondyliini (Diptera: Cecidomyiidae) associated with Bauhinia brevipes (Fabaceae) in Brazil - Maia, Valéria Cid; Fernandes, G. Wilson (Zootaxa, 2005)
Asphondylia microcapillata sp. n. and Schizomyia macrocapillata sp. n. are described and illustrated on the basis of the larva, pupa, male, female, and gall. Both species induce leaf galls on Bauhinia brevipes (Fabaceae).